Increased central auditory gain in 5xFAD Alzheimer’s disease mice as an early biomarker candidate for Alzheimer’s disease diagnosis - Na, Daxiang; Zhang, Jingyuan; Beaulac, Holly J.; Piekna-Przybylska, Dorota; Nicklas, Paige R.; Kiernan, Amy E.; White, Patricia M. (Frontiers in Neuroscience, 2023)
Alzheimer’s Disease (AD) is a neurodegenerative illness without a cure. All current therapies require an accurate diagnosis and staging of AD to ensure appropriate care. Central auditory processing disorders (CAPDs) and hearing loss have been associated with AD, and may precede the onset of Alzheimer’s dementia. Therefore, auditory dysfunction is a possible biomarker candidate for AD diagnosis. However, little is known about how auditory dysfunction and AD pathological changes are correlated. In the present study, we investigated the auditory dysfunctions in AD with transgenic amyloidosis mouse models. AD mouse models were bred on a CBA and C57BL/6 hybrid background, to compensate for the accelerated hearing loss on the C57BL/6background. Auditory brainstem response (ABR) recordings revealed significant hearing loss, a reduced ABR wave I amplitude, and increased central gain in 5xFAD mice. In comparison, these effects were milder or reversed in APP/PS1 mice. Longitudinal analyses revealed that in 5xFAD mice, central gain increase preceded ABR wave I amplitude reduction and hearing loss, suggesting that it may originate from lesions in the central nervous system rather than the peripheral loss. Analysis using publicly available datasets showed amyloid plaque deposited in the auditory cortical regions and upper auditory brainstem of 5xFAD mice, including the inferior colliculus (IC) and the medial geniculate body (MGB). This plaque distribution parallels histological findings from human subjects with AD. Pharmacologically facilitating cholinergic signaling with donepezil reversed the central hyperactivity in 5xFAD mice. After the central gain increased, aging 5xFAD mice developed deficits for hearing sound pips in the presence of noise, consistent with CAPD-like symptoms of AD patients. Overall, we conclude that auditory alterations in amyloidosis mouse models may correlate temporally with amyloid deposits in the auditory brainstem and may be reversed initially through enhanced cholinergic signaling. The alteration of ABR recording related to the increase in central gain prior to AD-related hearing disfunction suggests it could potentially be used as an early biomarker of AD diagnosis.